comparison of numerical methods used for finite element modelling of soft tissue deformation - Pathmanathan, P; Gavaghan, D; Whiteley, J (2009)
Soft tissue deformation is often modelled using incompressible non-linear elasticity, with solutions computed using the finite element method. There are a range of options available when using the finite element method, in particular the polynomial degree of the basis functions used for interpolating position and pressure, and the type of element making LIP the mesh. The effect of these choices oil the accuracy of the computed Solution is investigated, using a selection of model probl